Anaerobic microbial core for municipal wastewater treatment — the sustainable platform for resource recovery - Conall Holohan, B.; Trego, Anna; Keating, Ciara; Bressani-Ribeiro, Thiago; Chernicharo, Carlos L.; Daigger, Glen; Galdi, Stephen M.; Knörle, Ulrich; Paissoni, Eleonora; Robles, Angel; Rogalla, Frank; Shin, Chungheon; et al. (Elsevier, 2025)
The requirement for carbon neutrality and bioresource recovery has shifted our views on water treatment from health and pollution avoidance to one of sustainability with water and nutrient circularity. Despite progress, the current process of wastewater treatment is linear, based on core aerobic microbiology, which is unlikely to be carbon neutral due to its large use of energy and production of waste sludge. Here, we outline a shift from aerobic to anaerobic microbiology at the core of wastewater treatment and resource recovery, illustrating the state-of-the-art technologies available for this paradigm shift. Anaerobic metabolism primarily offers the benefit of minimal energy input (up to 50% reduction) and minimal biomass production, resulting in up to 95% less waste sludge compared with aerobic treatment, which is increasingly attractive, given dialogue surrounding emerging contaminants in biosolids. Recent innovative research solutions have made ambient (mainstream) anaerobic treatment a ready substitute for the aerobic processes for municipal wastewater in temperate regions. Moreover, utilising anaerobic treatment as the core carbon removal step allows for more biological downstream resource recovery with several opportunities to couple the process with (anaerobic) nitrogen and phosphorus recovery, namely, potential mainstream anaerobic ammonium oxidation (anammox) and methane oxidation (N-DAMO). Furthermore, these technologies can be mixed and matched with membranes and ion-exchange systems, high-value biochemical production, and/or water reuse installations. As such, we propose the reconfiguration of the wastewater treatment plant of the futurewith anaerobic microbiology. Mainstream anaerobic treatment at the core of a truly sustainable platform for modern municipal wastewater treatment, facilitating circular economy and net-zero carbon goals.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 31 Biological Sciences; 32 Biomedical and Clinical Sciences; 3106 Industrial Biotechnology; 3206 Medical Biotechnology; 3001 Agricultural Biotechnology; 12 Responsible Consumption and Production; 7 Affordable and Clean Energy; Biotechnology